Nematoides como indicadores de alterações ambientais em um rio com diferentes níveis de impacto antropogênico. - Lehun, Atsler Luana (2020)
Changes in the biodiversity of parasites communities can be used as indicators of the healthy ecosystem as they reflect environmental impacts through their responses to changes in habitat. Thus, the aim of the study was to investigate the potential use of parasites from Geophagus brasiliensis as bioindicators of environmental changes. Three sample points were determined of rio Iguaçu with different degrees of environmental impact. Among 69 specimes analyzed of G. brasiliensis, 32 (46.3%) were parasitized by at least one parasite. A total of 56 specimens of endoparasites belonging to the phylum Nematoda were collected. The abundance of nematode species was significantly higher in fishes collected in point 3 (Kruskal-Wallis2;69 = 8.62; p = 0.01) and species composition between points were significantly different (F = 6.95, p = 0.002). There was no significant difference in relative condition factor (Kn) of G. brasilienses between the points (F2;66 = 2.54; p = 0.08) there was no correlation in Kn and abundance of nematodes (rs = 0.1; p = 0.4). The lower abundance of nematodes was observed in point 1 (critically degraded), due to this environment showing changes in abiotic factors, represented in the relatively high values of conductivity and phosphorus when compared with points 2 and 3 (moderately degraded).The results obtained in the present study indicate that the parasitic community of G. brasiliensis is characterized by low diversity in polluted locations, thus the absence of certain species of parasites and the occurrence of nematode species demonstrated a variation in response to the pollution gradient.